(untitled) (Atti del Sodalizio Glottologico Milanese, 2024)
This study challenges the alleged parallel between Latin queo ‘I can’ and Sanskrit yā- ‘to be possible’. Though sharing some similarities (e.g., motion as a source domain, negative polarity contexts), they exhibit significant differences. Queo is personally constructed and typically conveys participant-related possibility, while yā-constructions are linked to agent demotion. The passive meaning of yā- in personal constructions and its possible connection to modality are also briefly addressed.